Transaction pricing paradoxes in the post-BEPS era - POLISHCHUK Сергій (Ius Modernum, 2025)
The current problems of transfer pricing that arise in the post-BEPS context are highlighted. Particular attention is paid to the harmonization of national approaches with international standards, the resolution of analytical controversies that arise in the process of implementing OECD recommendations, and the prospects for improving the methodology for evaluating transnational operations. The relevance of the topic is due to the increasing complexity of economic relations in the global environment, the strengthening of tax competition between jurisdictions and the need to create effective mechanisms to combat aggressive tax planning. The study is based on the hypothesis that the adaptation of global standards to local economic realities through the introduction of flexible and transparent mechanisms of transfer regulation will increase the efficiency of tax control and reduce the risks of tax disputes. The research methodology is based on a systematic approach to analysing the relationships between local and international practices of transfer pricing, as well as a comparative analysis aimed at evaluating the effectiveness of implementing OECD recommendations in different jurisdictions. The Ukrainian practices of adapting transfer pricing standards were studied, in particular, the implementation of documentation in accordance with OECD reporting (Country-by-Country Reporting), an analysis of legislative changes aimed at harmonizing the "armʼs length" principle and the features of a risk-based approach to tax control was carried out. Three main aspects of the transfer pricing issue were considered. Firstly, the transformation of the conceptual foundations of regulation, in particular, the analysis of the evolution of the "armʼs length" principle and approaches to ensuring tax transparency. It is established that, despite the universality of the principle, its practical application faces numerous challenges, especially in cases of valuation of intangible assets and risk allocation. Secondly, analytical controversies that arise in the process of implementing OECD standards are noted. Special attention is paid to regulatory collisions arising from discrepancies between local legislation and international recommendations, as well as paradoxes of economic profitability, in particular in the evaluation of inter-corporate transactions. The results of the study emphasize the importance of creating adaptive methods of functional analysis that take into account the specifics of industries and market conditions. Thirdly, a vision of prospects for solving the identified problems is formed. The integration of the concept of "antifragility" of economic systems as a tool for increasing the stability of transfer pricing to dynamic changes is proposed. Ways of intellectualizing methodologies are also considered, including the development of adaptive profitability assessment mechanisms and transparent reporting tool.